Papers on ELT for Asian Countries - Lim, Ho Peng (INTI Book Centre Sdn. Bhd., 1997)
Papers on ELT for Asian Countries is a collection of papers representing a range of topics, each dealing with a specific teaching or learning skill. Successful learning stems from effective teaching. This collection of papers offers some alternative to current classroom teaching techniques. Most of the ideas put forward in the papers have been adapted to suit both learners of English as a Second Language and English as a Foreign Language. It is hoped that English Language practitioners will find the papers interesting and relevant to their classroom needs. It is the aim of Papers on ELT for Asian Countries to provide a source of materials from which teachers can draw upon to stimulate interest and participation in the English Language classroom